2018
DOI: 10.3390/ijerph15122791
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mind-Body Exercise on Cognitive Performance in Elderly: A Systematic Review and Meta-Analysis

Abstract: Background: As the situation of cognitive aging is getting worse, preventing or treating cognitive decline through effective strategies is highly important. This systematic review aims to investigate whether mind-body exercise is an effective approach for treating cognition decline. Methods: Searches for the potential studies were performed on the eight electronic databases (MEDLINE, Scopus, Web of Science, SPORTDiscus, CINAHL, PsycArtilces, CNKI, and Wanfang). Randomized controlled trials (RCTs) examining the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 58 publications
1
78
1
2
Order By: Relevance
“…Nevertheless, MBI involving meditative movements already showed that they are suitable for the special needs of older adults as a target group [ 6 , 11 ]. That’s why the latest findings considered MBI involving meditative movements as being feasible and effective for all ages [ 11 , 12 , 13 , 14 , 15 ]. Furthermore, MBI involving meditative movements attracted researchers’ attention because of their effectiveness in treating depression and various chronic illnesses, including stress, acute and chronic pain, cardiovascular disease and hypertension in the adult population [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, MBI involving meditative movements already showed that they are suitable for the special needs of older adults as a target group [ 6 , 11 ]. That’s why the latest findings considered MBI involving meditative movements as being feasible and effective for all ages [ 11 , 12 , 13 , 14 , 15 ]. Furthermore, MBI involving meditative movements attracted researchers’ attention because of their effectiveness in treating depression and various chronic illnesses, including stress, acute and chronic pain, cardiovascular disease and hypertension in the adult population [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have also been interested in examining the neurocognitive benefits of TC [30]. Notably, the majority of early studies mainly focused on the effects of TC on behavioral outcome measures related to cognition [31,32]. With recent advances in neuroimaging techniques, scholars started to pay great attention to understanding the neurobiological mechanisms and processes underlying the cognitive protective effects of TC, suggesting that patients with brain damage demonstrate neuropsychological improvements after practicing TC [33].…”
Section: Of 11mentioning
confidence: 99%
“…Except that the rst question is not scored, each remaining item is scored 1 point, a total of 10 points. The scoring criteria are: 9-10 points are excellent, 6-8 points are good, 4-5 points are fair, and below 4 points are poor [37].…”
Section: Literature Quality Evaluationmentioning
confidence: 99%